Apparent digestibility coefficients of selected protein ingredients for juvenile Totoaba macdonaldi - Jorge Madrid; Camilo Pohlenz; María Teresa Viana; Juan Pablo Lazo (Journal of the World Aquaculture Society, 2023)
Abstract Two feeding trials were performed to evaluate the apparent digestibility coefficients (ADCs) of dry matter, protein, and amino acids of three animal‐origin and four plant‐origin ingredients in Totoaba macdonaldi. In the first feeding trial, the animal‐origin ingredients were evaluated using totoaba juveniles with an initial weight of 529.7 ± 104.2 g, and for the second feeding trial 745.9 ± 210.6 g. Evaluated ingredients were: poultry by‐product meal, meat and bone meal, feather meal (FM), soy protein concentrate, soybean meal (SBM), corn gluten (CG), and wheat gluten (WG). Each experimental ingredient was evaluated in triplicate. ADCs of dry matter ranged from 35.9% for FM to 67.9% for poultry by‐product, while the protein ADCs values ranged from 41.7% for CG to 83.2% for poultry by‐product. Fish meal ADC (79.6%) was similar to poultry by‐product but significantly higher than WG and soy protein concentrate (72.5% and 72.6%, respectively). The ADCs for lysine were significantly higher for WG, sardine meal, poultry by‐product, and SMB (94.5%, 79.8%, 79.4%, and 79.4%, respectively). Based on the results from the present study, poultry by‐product, WG, and soy protein concentrate are the most promising alternative ingredients (i.e., to the fishmeal) for the formulation of totoaba grow‐out feeds.